2010
DOI: 10.1002/art.27415
|View full text |Cite
|
Sign up to set email alerts
|

Synovial tissue heterogeneity in rheumatoid arthritis in relation to disease activity and biomarkers in peripheral blood

Abstract: Objective To investigate the clinical relevance of synovial tissue subtypes in rheumatoid arthritis (RA) and to search for peripheral blood (PB) markers that may serve as biomarkers for tissue subtypes. Methods Gene expression analysis using complementary DNA microarrays was applied on paired synovial tissue biopsy and PB samples obtained from 17 RA patients. Molecular tissue subtypes were correlated with histologic parameters (CD3, CD22, CD38, CD68, CD163, tumor necrosis factor α, intercellular adhesion molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 15 publications
14
58
0
Order By: Relevance
“…Different subtypes of RA patient synovia have also been characterised by gene expression analysis. 112,113 Geneexpression variance among RA patients has been described impacting several pathways involved in cell proliferation, cell survival, angiogenesis and regulation of inflammation. 114 …”
Section: Recent Advancesmentioning
confidence: 99%
“…Different subtypes of RA patient synovia have also been characterised by gene expression analysis. 112,113 Geneexpression variance among RA patients has been described impacting several pathways involved in cell proliferation, cell survival, angiogenesis and regulation of inflammation. 114 …”
Section: Recent Advancesmentioning
confidence: 99%
“…A recent study by van Baarsen et al has shown that a high inflammatory synovial gene-expression profile correlates with a higher disease activity, C reactive protein (CRP) levels and erythrocyte sedimentation rates (ESRs), increased platelet numbers and a shorter disease duration in RA patients 12. This indicates that there is a diagnostic value of determining low and high inflammatory subtypes of synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Van Baarsen and colleagues studied the synovial tissue gene expression profiles in relation to immunohistochemical scores and disease parameters. The results demonstrated an excellent correlation between molecular and immunohistochemical scoring (van Baarsen et al, 2010b). Moreover, the high inflammation tissue type was predominantly observed in patients with high disease activity and short disease duration, suggesting temporal differences in the inflammatory status during the course of the disease (Firestein & Zvaifler, 2002).…”
Section: Genes and Signatures Involved In Disease Activitymentioning
confidence: 69%
“…The identification of processes and biomarkers in PB may facilitate informative studies of a relation between tissue type and clinical parameter. The notion that molecular heterogeneity is present in both the synovial as well as the PB compartment makes it tempting to speculate on molecular and biological features that reflect the tissue pathology (van Baarsen et al, 2010b). However, paired analysis of peripheral blood and affected synovium from 17 patients with RA revealed that differential tissue pathology was not reflected in the PB by differential expression of single genes.…”
Section: Gene Expression Heterogeneity In Blood Vs Synovial Tissuementioning
confidence: 99%